Optical and Morphological Studies on Novel Polyaniline-P2O5 Conductive Polymer Composites - Satheeshkumar1, P.; Kalaivani2, A.; Senguttuvan1, G.; Sivakumar1, V.; Surendra Dilip3, C. (Asian Journal of Chemistry, 2013)
Recently conducting polymer composites have attracted considerable interest due to their numerous applications. Present work reports the preparation of polyaniline polymeric material with P2O5 to form polyaniline-P2O5 composites by chemical oxidation method. FTIR analysis established the various modes of vibration due to diverse functional groups present in the composite and the presence of a strong interaction between P2O5 and polyaniline. The UV-VIS spectra confirmed the p-p* and n-p* transitions of the benzenoid and quinonoid structure of the composites. The linear optical nature was understood from the optical transmission spectrum. The XRD patterns exhibited a weak crystalline nature for the composites. Thermal stability of polyaniline-P2O5 was determined using TGA. The SEM images show the effect of P2O5 doping and on polyaniline morphology. EDAX was performed to confirm the presence of P2O5 and polyaniline. Surface topography of polyaniline-P2O5 composites were studied using AFM.